Clinical-psychopathological and psychometric features of maladaptive disorders which are a characteristic of students who have experienced psycho-emotional stress - A.I. Sharun; L.M. Yuryeva (Medičnì Perspektivi, 2022)
The purpose of this study is to discover the most relevant psychopathological features of maladaptive disorders arising under the influence of psycho-emotional stress in the student community and associated with consequences of military conflict, and identify potential diagnostic and treatment-rehabilitation measures for improving effectiveness of their primary, secondary and tertiary prevention in future. The study was conducted in 4 stages on the basis of an adapted questionnaire and a set of psychometric methods, involving 249 adult students (over 18 years), including a group of respondents at greatest risk – and namely students who are internally displaced persons and students children of anti-terrorist operation participants. The studies have shown a decrease in psychological well-being, the predominance of leading psychopathological symptoms of anxiety, lack of interest in life, lack of motivation, loss of vital energy, feelings of hopelessness, suicidal thoughts, somatic symptoms in the form of disorders of the cardiovascular, gastrointestinal systems, higher medium severity levels of asthenic manifestations; worse than the general indicator of quality of life among the respondents of the main group. Inverse correlation between a high level of state anxiety (r= -0.6) and trait anxiety (r= -0.45) and a low level of mental well-being has been proved. The obtained results can be used to substantiate and continue transformation of the system of social and medical support in health care, in particular when developing measures aimed at preventing development of non-psychotic mental disorders among students in Ukraine, which will optimize human resources and further health improvement of student youths.